Construção de identidade de marca, fotografia de moda e erotismo: As campanhas Sisley. - SILVA, Vivianne Cabral e (2007)
This dissertation was developed to the effect to discuss the relations establish and noticed at the present time, between fashion photography and eroticism. Resumedly proposes the analysis of Sisley s advertising campaign, with focus in the importance and meaning of such cultural expressions for the establishment of its identity before its consumers.